Effect of targeted ovarian cancer immunotherapy using ovarian cancer stem cell vaccine. Issue 1 (December 2015) - Wu, Di; Wang, Jing; Cai, Yunlang; Ren, Mulan; Zhang, Yuxia; Shi, Fangfang; Zhao, Fengshu; He, Xiangfeng; Pan, Meng; Yan, Chunguang; Dou, Jun
Abstract Background Accumulating evidence has shown that different immunotherapies for ovarian cancer might overcome barriers to resistance to standard chemotherapy. The vaccine immunotherapy may be a useful one addition to conditional chemotherapy regimens. The present study investigated the use of vaccine of ovarian cancer stem cells (CSCs) to inhibit ovarian cancer growth. Methods CD117+ CD44+ CSCs were isolated from human epithelial ovarian cancer (EOC) SKOV3 cell line by using a magnetic-activated cell sorting system. Pre-inactivated CD117+ CD44+ CSC vaccine was vacccinated into athymic nude mice three times, and then the mice were challenged subcutaneously with SKOV3 cells. The anti-tumor efficacy of CSC vaccine was envaluated by in vivo tumorigenicity, immune efficient analysis by flow cytometer, and enzyme-linked immunosorbent assays, respectively. Results The CD117+ CD44+ CSC vaccine increased anti-ovarian cancer efficacy in that it depressed ovarian cancer growth in the athymic nude mice. Vaccination resulted in enhanced serum IFN-γ, decreased TGF-β levels, and increased cytotoxic activity of natural killer cells in the CD117+ CD44+ CSC vaccine immunized mice. Moreover, the CSC-based vaccine significantly reduced the CD117+ CD44+ CSC as well as the aldehyde dehydrogenase 1 positive cell populations in the ovarian cancer tissues in the xenograft mice. Conclusion The present study provided the first evidence that human SKOV3 CD117+ CD44+ CSC-based vaccine may induce the anti-ovarian cancer immunity against tumor growth by reducing the CD117+ CD44+ CSC population.